Efeito simultâneo da deficiência hídrica e do alumínio tóxico no solo na cultivar IAC91-5155 de cana-de-açúcar - Carlin, Samira Domingues; de Lima Rhein, Andressa Freitas [UNESP]; Mathias dos Santos, Durvalina Maria [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Sugarcane is a very important economic crop in Brazil. The effects of abiotic stresses cause negative reduction of the productivity in the sugarcane industry. In order to identify indicators of stresses tolerance, two physiological variables were evaluated, nitrate reductase activity and chlorophyll contents in young plants of sugarcane, cv. IAC91-5155. The simultaneous effect of abiotic stresses of high occurrence in Brazilian soils are, water deficiency and aluminum toxicity. The plants were submitted to three treatments of water availability (% field capacity, FC): no stress (70% FC), moderate stress (55% FC), and extreme stress (40% FC); and three acidity treatments in the soil (base saturation, V%): no acidity (V=55%), average acidity (V=33%), and high acidity (V=23%). The experiment was carried out in greenhouse, with 29.7 +/- 4.3 degrees C and 75 +/- 10% RH. The experimental design was in randomized blocks, in 3x3 factorial arrangement, with four replicates. After 60 days, nitrate reductase activity and chlorophyll contents were evaluated in the diagnostic leaf. The results demonstrate that the response of plants to a combination of drought and aluminum toxicity, similar to the conditions in many natural environments, is different from the response of plants to each of these stresses applied individually, as typically tested in the laboratory. The nitrate reductase activity can be used as a biochemical-physiological marker of water deficiency while chlorophyll contents can be used as a biochemical-physiological marker of both of them, water deficiency or aluminum toxicity in soil. Both parameters can not be as a biochemical-physiological marker for acclimation of young plants of sugarcane cv. IAC91-5155, under the combined stresses.
Simultaneous effect of water deficiency and aluminum toxicity in the soil in cultivar IAC91-5155 of sugarcane
Keywords: Saccharum spp.; Nitrate reductase; Chlorophylls; water deficit; Acidity